การสื่อสารการตลาดผ่านผู้มีอิทธิพลทางความคิดบนอินสตาแกรมของผลิตภัณฑ์เสื้อผ้าแฟชั่นแบรนด์ไทย - ณัชชา จริยธรรมานุกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This research was mixed methods. A qualitative research was used, which included document from 1,210 fashion Thai brand’s Instagram posts and in-depth interviews with 3 brand owners to analyze strategies and marketing communication through influencers. In addition, quantitative study using survey research methods with online questionnaire to collect data from 400 participants aged 18 to 30 years to investigate and explain the correlation between communication exposure, attitudes toward influencers, and purchase decisions.According to the research, fashion Thai brands on Instagram use influencers with Asian appearance and lifestyles that are consistent with the brand s identity for marketing communication. Presented with Carousels post displaying a half-body portrait, notice the face clearly and express themselves naturally in a natural setting background with bright tones. The content is frequently a general informational of the product, including popular phrases in the descriptions. Additionally, it was observed that a shot video with a duration of less than 15 seconds received a customer feedback by being viewed and expressed their opinions by clicking Like and comments on the Carousels post with the Emoji and positive phrases. Furthermore, the samples had highly positive attitude toward influencers. Use of thought influencers whose lifestyles are similar to the brand s will make the product more interesting.The hypothesis testing revealed that exposure to fashion Thai brands marketing communication via influencers on Instagram was related with attitudes toward thought influencers, and attitudes toward thought influencers were associated with purchasing decisions. It was a positive correlation that was statistically significant at the.01 level.